Thermodynamic and magnetic properties of the layered triangular magnet NaNiO2 - Baker, P; Lancaster, T; Blundell, S; Brooks, M; Hayes, W; Prabhakaran, D; Pratt, F (American Physical Society, 2005)
We report muon-spin rotation, heat capacity, magnetization, and ac magnetic susceptibility measurements of the magnetic properties of the layered spin-1/2 antiferromagnet NaNiO2. These show the onset of long-range magnetic order below TN=19.5 K. Rapid muon depolarization, persisting from TN to about 5 K above TN, is consistent with the presence of short-range magnetic order. The temperature and frequency dependence of the ac susceptibility suggests that magnetic clusters persist above 25 K and that their volume fraction decreases with increasing temperature. A frequency dependent peak in the ac magnetic susceptibility at Tsf=3 K is observed, consistent with a slowing of spin fluctuations at this temperature. A partial magnetic phase diagram is deduced.